Influence of life-purpose on treatment compliance among selected asthma patients in Nigeria, (2005)
"This study investigated the relationship of life-purpose and treatment compliance in 137 asthma patients from a hospital in Nigeria. Patient ages ranged from 15 to 75 years (M = 44.6, SD = 15.2). The Life Purpose Questionnaire and a questionnaire that was designed to assess treatment compliance among asthma patients were used for this study. Results indicated a statistically significant, positive correlation between life purpose and treatment compliance of the asthma patients [r (135) = 0.20, P < 05]. These findings support the hypothesis that life-purpose may have some positive relationship with treatment compliance. We therefore speculate that effective asthmatic care and management should include psychological and logotherapeutic interventions."